Henry and the paper route - Cleary, Beverly; Darling, Louis (New York : Morrow, 1957)
When Henry wants to start a paper route, he receives unexpected help from a little girl, Ramona.
U
820L
Accelerated Reader
Accelerated Reader AR
edited hb 2015-06-16
Keywords: Newspaper carriers; Humorous stories; Huggins, Henry (Fictitious character) -- Fiction; Huggins, Henry (Fictitious character); Siblings; Fiction; Fiction